Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan Faste Coffe Rajabasa - Risha Khairani; Vinka Khoirul Winanda; Nabilla Sevtiana Putri; Aldi Pranoto; Rima Amalia Cahya; Rahmawati (STKIP Subang, 2025)
Faste Coffee Rajabasa customers stated that they were dissatisfied and reluctant to make repeat purchases because the quality of service provided was relatively low. The purpose of this study was to determine the effect of service quality on Faste Coffee Rajabasa customer satisfaction. This study is a type of quantitative research that uses a descriptive verification method with an ex post facto approach and survey. The population of this study was Faste Coffee Rajabasa consumers who had made purchases at least twice in the last two months, which were then sampled using accidental sampling techniques and obtained 76 respondents. Data collection techniques were carried out through observation, questionnaires, and interviews. Instrument testing was carried out with a validity test using the Pearson Product Moment formula and reliability using the Cronbach's Alpha formula, while the analysis prerequisite test included normality and homogeneity tests. The classical assumption tests used included linearity, multicollinearity, autocorrelation, and heteroscedasticity tests. Hypothesis testing was carried out using simple linear regression through the t-test and coefficient of determination (R Square). The results of the t-test show that the calculated t value is 2.612> t table 1.993, with a significance value of 0.011 <0.05. This indicates that H₀ is rejected and H₁ is accepted. Thus, it can be concluded that there is a positive and significant influence of service quality on customer satisfaction at Faste Coffee Rajabasa. The coefficient of determination (R Square) value is 0.176, which means that 17.6% of customer satisfaction is influenced by service quality, while the other 82.4% is influenced by other variables not examined in this study.